EP1009 Loss of skeletal muscle mass during neo-adjuvant chemotherapy and the relation to survival in patients with ovarian cancer; a prospective analysis of the OVHIPEC-1 cohort. (1st November 2019) - Ubachs, J; Koole, S; Bruijs, L; Lahaye, M; Fabris, C; Schagen van Leeuwen, J; Schreuder, H; Hermans, R; de Hingh, I; van der Velden, J; Arts, H; Massuger, L; et al.
Abstract : Introduction/Background: Skeletal muscle depletion in women with advanced ovarian cancer has been associated with adverse clinical outcome and survival. To validate earlier results in a homogenous population, we analyzed whether a decrease in skeletal muscle index (SMI) during neo-adjuvant chemotherapy (NACT) is associated with worse outcome in patients with stage III epithelial ovarian cancer, who were included in the OVHIPEC trial. Methodology: Within the phase III OVHIPEC trial, 245 patients with stage III ovarian cancer were randomized after three cycles of NACT with carboplatin and paclitaxel to receive interval cytoreductive surgery (CRS) with or without HIPEC. Randomization was performed after at least stable disease after two cycles of NACT, and when complete or optimal CRS was achieved. CT-scans performed at baseline (timepoint 1), and after two cycles of NACT (timepoint 2) were selected. A slide on the third lumbar level was selected from each CT-scan, and the difference in SMI between both scans (ΔSMI) was calculated using SliceOMatic. Overall and recurrence-free survival of patients with a decrease or increase in ΔSMI were performed using Kaplan-Meier estimates and log-rank tests. Results: Of the 245 patients randomized in the OVHIPEC trial, SMI and ΔSMI of scans at both timepoints were available for 212 patients (87%). After a median follow-up of 4.7 years, 116 of 212 patients (55%) had died. In survival analysis, 43 of 74 patients (58%) in the group with a decrease in ΔSMI, and 73 of 138 of the patients (53%) in the group with stable/increase in ΔSMI had died. Median overall survival did not differ significantly(p=0.764). Conclusion: A decreasing skeletal muscle index during neo-adjuvant chemotherapy was not associated with worse outcome in patients with stage III ovarian cancer, who were treated with complete/optimal interval CRS and six cycles of chemotherapy within the OVHIPEC trial. Disclosure: Nothing to disclose.